2020
DOI: 10.1186/s41118-020-00084-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Religion and Unintended Childbearing in Nigeria: A Cross-Regional Perspective

Abstract: Context: Childbearing remains a global public health issue, posing an enormous challenge to families, communities, governments, program managers, and researchers, especially in developing countries. Objective: The study examines the influence of religion on women's experience of unintended childbearing in Nigeria. Method: Using the 2018 Demographic and Health Survey, the analysis focused on 13,109 women of reproductive age who had a birth within 2 years preceding the date of the interview. Multivariate logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Regional variation was found across the six geopolitical zones with the Northwest zone found with the highest number of women within the ages of 40-49 with desire for another child. This result is in line with that of Oyediran, Ishola, and Bankole (2020) which indicates that the regional environmental dynamics where women live have impact on their decision on childbearing.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…Regional variation was found across the six geopolitical zones with the Northwest zone found with the highest number of women within the ages of 40-49 with desire for another child. This result is in line with that of Oyediran, Ishola, and Bankole (2020) which indicates that the regional environmental dynamics where women live have impact on their decision on childbearing.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…In this study, slightly below 90% of the couples planned their fertility. The percentage of unplanned fertility is a bit closer to 13% of women -stated by Oyediran et al (2020)-who reported that they had unintended childbirths in the last two years.…”
Section: Discussionmentioning
confidence: 71%
“…This conservative belief system which finds itself in a region that predominantly favors the polygamous family system is likely to trivialize fertility planning. Moreover, the pronatalist nature of Islam in the north is a major driver of the orientation and belief system that procreation is so divinely controlled that fertility cannot be planned by a man in addition to the belief that a child journey into the word is divinely designed (Oyediran et al, 2020), thereby implying that children are divine blessings and should always be expected. The lack of planned fertility status in the north could also be attributed to the hitherto low level of education, high poverty level, the ubiquity of early/child marriage, and preponderance of polygyny in the region (Odusina et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to stress often associated with an urban lifestyle that may contribute to the aggressiveness of relationships (Litman, 2017). In addition, the breakdown in the traditional values in urban areas could make men more vulnerable to conflict in their intimate relationship if they expect their spouses to be subservient as patriarchal norms dictate (Beebeejaun, 2017; Oyediran & Odusola, 2004; Oyediran et al, 2020). The difficulty for some rural men to earn enough livelihood to support their families’ needs may lead to a tense home environment.…”
Section: Discussionmentioning
confidence: 99%